Elshad, Aliyev - (:unkn) unknown (My University, 2026)
Elshad Aliyev specializes in the application of information and communication technologies (ICT) in the field of artistic creativity. In 2014, he successfully defended his doctoral dissertation entitled "The Internet and the Dynamics of the Development of the Artistic Process," and in 2016 he was awarded the degree of Doctor of Philosophy (PhD) in Art Studies. His research also focuses on representations of the Safavids in 15th–17th century European art, with particular emphasis on portraits of Shah Ismail Safavi. He was the first scholar to undertake a comprehensive academic study of the historic portrait of Shah Ismail Safavi preserved in the Uffizi Gallery in Florence, Italy. As part of this research, he conducted studies in libraries, museum collections, and archives in several Italian cities during research visits in 2019, 2022, and 2023. In 2016, he was awarded a grant under the Science–Education Integration Grant Competition of the Science Development Foundation of Azerbaijan. He has also participated in several international research projects. In 2023, Dr. Aliyev became one of the co-authors of the collective monograph The Giovio Collection, published by the renowned Italian publishing house Giunti Editore. He is also the author of three scholarly monographs.